Lactate dehydrogenase predicts disease progression outcome in COVID-19 patients treated with Azvudine - Mao, Manyun; Dian, Yating; Sun, Yuming; Chen, Wangqing; Zhu, Wu; Deng, Guangtong (Frontiers in Cellular and Infection Microbiology, 2023)
Background Azvudine has been approved in China for the treatment of COVID-19 patients. Previous studies have suggested a correlation between high levels of lactate dehydrogenase (LDH) and the severity of COVID-19. However, the impact of LDH levels in COVID-19 patients receiving Azvudine treatment remains unclear. Methods In this retrospective cohort study, we analyzed the data of 351 hospitalized COVID-19 patients who were consecutively treated with Azvudine, with or without high LDH levels. The clinical features, treatment strategies and prognosis data were collected and analyzed. Results Among the 351 hospitalized patients with COVID-19 treated with Azvudine (119 with high-LDH levels), the median age was 69 years (range 58–78), and 213 (60.7%) were male. Common symptoms included cough (86.0%), expectoration (73.5%), fever (69.8%), polypnea (47.6%) and poor appetite (46.4%). Patients with high LDH levels exhibited significantly elevated leucocyte and neutrophil counts, elevated level of myocardial enzymes, as well as higher levels of inflammatory markers such as interleukin-6, interleukin-10, procalcitonin, C reactive protein, ferritin, and prolonged erythrocyte sedimentation rate upon admission. COVID-19 patients with high-LDH levels had higher rates of corticosteroid therapy, non-invasive and invasive mechanical ventilation, worsened and death (2.5% vs. 0%). The Cox proportional hazard model demonstrated that high LDH levels (adjusted hazard ratio = 5.27; 95% confidence interval: 1.19, 14.50) were associated with a more unfavorable composite disease progression outcome among COVID-19 patients treated with Azvudine, after accounting for potential confounding variables. Conclusion High-LDH levels predict a worse composite disease progression outcome in COVID-19 patients treated with Azvudine.